2021
DOI: 10.3233/cbm-203043
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of protein-based salivary markers in the diagnosis of oral potentially malignant disorders: A systematic review and meta-analysis

Abstract: By using a meta-analytical approach, this study aimed to analyse the diagnostic capacity of protein-based biomarkers in saliva for the differential diagnosis of oral potentially malignant disorders (OPMDs) and oral squamous cell carcinoma (OSCC) from healthy individuals as control group (HCG). Articles on protein-based biomarkers in saliva, which provided quantitative expression in individuals with clinical and histopathological diagnosis of OPMD or oral leukoplakia (OL) were considered eligible. Searches were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Arroyo et al [139] in a recent meta-analysis found 11 biomarkers of which they did meta-analysis for 4. Of these, only carcinoembryonic antigens (CEA) and soluble fragment of cytokeratin 19 (CYFRA21) were found to be significantly associated with oral cancer.…”
Section: Carcinogenesismentioning
confidence: 99%
“…Arroyo et al [139] in a recent meta-analysis found 11 biomarkers of which they did meta-analysis for 4. Of these, only carcinoembryonic antigens (CEA) and soluble fragment of cytokeratin 19 (CYFRA21) were found to be significantly associated with oral cancer.…”
Section: Carcinogenesismentioning
confidence: 99%
“…In the field of omics sciences, the role of salivary proteins associated with OSCC has been widely investigated. Various systematic reviews and meta-analyses have recently summarized this research topic’s state of the art [ 168 , 169 , 170 , 171 , 172 ].…”
Section: Resultsmentioning
confidence: 99%
“…In detail, Arroyo et al [ 172 ] analyzed the diagnostic capacity of salivary proteins as biomarkers for the differential diagnosis of OPMDs and OSCC compared to healthy controls. Their research was published in 2021 and considered, at the end of the selection, eight papers eligible for their purpose, thus reporting a series of potential markers, of which those significantly higher in OSCC/OPMDs than healthy controls, and therefore with diagnostic significance, were carcinoembryonic antigen (CEA) [ 173 , 174 ] and the soluble fragment of cytokeratin 19 (CYFRA21) [ 170 , 171 ].…”
Section: Resultsmentioning
confidence: 99%
“…Minimally invasive technologies for OPMD detection should be prioritized. For pathological diagnosis, the current gold standard, we should (i) develop standardized histopathological criteria encompassing the various histological appearances for reliable diagnosis of OPMD; (ii) implement validated immunohistochemical and molecular biomarkers; (iii) incorporate artificial intelligence for diagnostic support; and (iv) develop and implement objective detection techniques as well as non-invasive alternatives to biopsies (buccal brushes, saliva, buccal rinses, optical techniques) [ 83 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%